2017
DOI: 10.1093/logcom/exx018
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorics of $\lambda$-terms: a natural approach

Abstract: We consider combinatorial aspects of λ-terms in the model based on de Bruijn indices where each building constructor is of size one. Surprisingly, the counting sequence for λ-terms corresponds also to two families of binary trees, namely black-white trees and zigzag-free ones. We provide a constructive proof of this fact by exhibiting appropriate bijections. Moreover, we identify the sequence of Motzkin numbers with the counting sequence for neutral λ-terms, giving a bijection which, in consequence, results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Should there be fewer abstractions than n + 1, then n represents a free variable occurrence. And so, in the De Bruijn notation both λxyz.xz(yz) and λabc.ac(bc) admit the same representation λλλ.20 (10), see Figure 1.…”
Section: 2mentioning
confidence: 97%
“…Should there be fewer abstractions than n + 1, then n represents a free variable occurrence. And so, in the De Bruijn notation both λxyz.xz(yz) and λabc.ac(bc) admit the same representation λλλ.20 (10), see Figure 1.…”
Section: 2mentioning
confidence: 97%
“…The following results exhibit the closed-form of generating functions corresponding to pure terms as well as the general class of λυ-terms and explicit substitutions. Proposition 6.2 (see [5]). Let L ∞ (z) denote the generating function corresponding to the set of λ-terms in υ-normal form (i.e.…”
Section: (K)mentioning
confidence: 99%
“…Enumeration. In the current paper we follow [7,8,27,15] and investigate the statistical properties of random λ-terms in the de Bruijn representation. We assume a unary base encoding of indices, i.e.…”
Section: 11mentioning
confidence: 99%
“…Investigations into quantitative properties of λ-terms in the de Bruijn notation were continued by Bendkowski et al [7,8] who showed that, in contrast to the canonical representation of David et al, asymptotically almost all λ-terms are not strongly normalising. In other words, the proportion of terms for which all evaluation strategies terminate approaches zero as the term size tends to infinity.…”
mentioning
confidence: 99%